Influence of interface dipole layers on the performance of graphene field effect transistors. (November 2019) - Nagamura, Naoka; Fukidome, Hirokazu; Nagashio, Kosuke; Horiba, Koji; Ide, Takayuki; Funakubo, Kazutoshi; Tashima, Keiichiro; Toriumi, Akira; Suemitsu, Maki; Horn, Karsten; Oshima, Masaharu
Abstract: The linear band dispersion of graphene's bands near the Fermi level gives rise to its unique electronic properties, such as a giant carrier mobility, and this has triggered extensive research in applications, such as graphene field-effect transistors (GFETs). However, GFETs generally exhibit a device performance much inferior compared to the expected one. This has been attributed to a strong dependence of the electronic properties of graphene on the surrounding interfaces. Here we study the interface between a graphene channel and SiO2, and by means of photoelectron spectromicroscopy achieve a detailed determination of the course of band alignment at the interface. Our results show that the electronic properties of graphene are modulated by a hydrophilic SiO2 surface, but not by a hydrophobic one. By combining photoelectron spectromicroscopy with GFET transport property characterization, we demonstrate that the presence of electrical dipoles in the interface, which reflects the SiO2 surface electrochemistry, determines the GFET device performance. A hysteresis in the resistance vs. gate voltage as a function of polarity is ascribed to a reversal of the dipole layer by the gate voltage. These data pave the way for GFET device optimization. Graphical abstract: Image 103146223